2004
DOI: 10.1080/0307945042000220679
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with colibacillosis outbreaks in caged layer flocks

Abstract: Colibacillosis appears to be of increasing significance in layer flocks, but there have been no studies of the risk factors associated with outbreaks. This study aimed to investigate the possible associations between risk factors of non-infectious nature and outbreaks of mortality due to colibacillosis in flocks of caged layer hens. Information on management, biosecurity measures and housing conditions was collected in 20 flocks suffering from the disease and in 20 clinically healthy control flocks. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 12 publications
(20 reference statements)
5
46
0
Order By: Relevance
“…Colibacillosis is a disease of severe economic significance to all poultry producers worldwide and is characterized by a diverse array of lesions. Recent reports in Western Europe implicate a resurgence of this disease in the poultry industry, particularly in chicken layers (Zanella et al, 2000;Vandekerchove et al, 2004;Jordan et al, 2005). Depending on the virulence status of the strain, host status and presence and type of predisposing factors, the infection manifests as an initial septicaemia that is followed by either sudden death or localized inflammation in multiple organs.…”
Section: Introductionmentioning
confidence: 99%
“…Colibacillosis is a disease of severe economic significance to all poultry producers worldwide and is characterized by a diverse array of lesions. Recent reports in Western Europe implicate a resurgence of this disease in the poultry industry, particularly in chicken layers (Zanella et al, 2000;Vandekerchove et al, 2004;Jordan et al, 2005). Depending on the virulence status of the strain, host status and presence and type of predisposing factors, the infection manifests as an initial septicaemia that is followed by either sudden death or localized inflammation in multiple organs.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, E. coli has been regarded as an opportunistic pathogen, and colibacillosis regarded a secondary disease following a primary infection (Dwars et al, 2009) or lack of appropriate management (Vandekerchove et al, 2004b). However, an increased significance, and a primary rather than secondary role of APEC in layers, has been reported both from the Netherlands and Denmark (Vandekerchove et al, 2005;Gregersen et al, 2010a).…”
mentioning
confidence: 99%
“…Impaired biosecurity protocols on farms which allow birds to contact wild birds, rodents, insects or any other wild animals are potential risk factors for APEC infections (Jiang et al 2014;Wang et al 2013). Generally, the animals and insects act as vectors to introduce and/or spread the disease among flocks (Barnes, 2013;Vandekerchove et al 2004a). It is not only the wild animal that can introduce colibacillosis, but infectious diseases can also be introduced through feed, hence strict biosecurity measures for feed are paramount (Vandekerchove et al, 2004;Wang et al, 2013).…”
Section: Risk and Predisposing Factors Associated With Avian Colibacimentioning
confidence: 99%
“…A number of overseas studies identified vectors humans (farm worker and visitors), wild birds and rodents, source and type of treatment(s) applied to the drinking water and unfavourable housing conditions as major risk factors associated with avian colibacillosis (Kemmett et al, 2013;Nolan et al, 2013;Vandekerchove et al, 2004a). Low levels of APEC on overseas poultry farms, is associated with strict farm biosecurity and management practices, such as control of vectors by minimising bird interaction with other animals and hygienic cleaning protocols Vandekerchove et al, 2004a;Zanella et al, 2000). However, little knowledge is available in regards to the potential predisposing risk factors (biosecurity and farm manageme nt protocols and environmental factors) associated with APEC among commercial broiler chicken flocks in Australia.…”
Section: Chapter 1: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation